1998
DOI: 10.1038/29972
|View full text |Cite
|
Sign up to set email alerts
|

New specimens and confirmation of an early age for Australopithecus anamensis

Abstract: The discovery of Australopithecus anamensis fossils from strata lying between tephra dated at 4.17 and 4.12 million years ago, and from slightly higher strata not well constrained in age by overlying dated units, provoked the claim that more than one species might be represented: it was suggested that the stratigraphically higher fossils, which include the important tibia, humerus and a large, presumed male, mandible (KNM-KP 29287), might belong to a later, more derived hominid. We have recovered new fossils f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 240 publications
(143 citation statements)
references
References 8 publications
2
139
0
2
Order By: Relevance
“…1) are Sahelanthropus tchadensis from Chad (about 7 Mya (65) ) and Orrorin tugenensis from Kenya (about 6-5·7 Mya (66) ). The next oldest are Ardipithecus kadabba (Ethiopia, about 5·8 Mya (67) ) and A. ramidus (Ethiopia, about 4·4 Mya (68) ), Australopithecus anamensis (Kenya, about 4·1-3·9 Mya (69) ), Au. afarensis (Ethiopia, Tanzania and maybe Kenya, 3·6 -3·0 Mya (70,71) ), Au.…”
Section: Human Evolutionmentioning
confidence: 99%
“…1) are Sahelanthropus tchadensis from Chad (about 7 Mya (65) ) and Orrorin tugenensis from Kenya (about 6-5·7 Mya (66) ). The next oldest are Ardipithecus kadabba (Ethiopia, about 5·8 Mya (67) ) and A. ramidus (Ethiopia, about 4·4 Mya (68) ), Australopithecus anamensis (Kenya, about 4·1-3·9 Mya (69) ), Au. afarensis (Ethiopia, Tanzania and maybe Kenya, 3·6 -3·0 Mya (70,71) ), Au.…”
Section: Human Evolutionmentioning
confidence: 99%
“…As recently as the mid-1960s (2), the African apes were considered to be distant relatives of the human lineage, but subsequent molecular phylogenetic analyses have shown that the chimpanzee and human are sister species and have led to a revision of the age of their divergence (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Currently, the earliest unequivocal upright hominids at 4.2 millions of years ago (Ma) provide the minimum age for human-chimpanzee divergence (14), and some recently proposed early hominids dated between 5 and slightly more than 6 Ma are thought to provide an estimate close to the actual species divergence (15)(16)(17)(18)(19). However, a divergence time of 12.5 Ma for humans and chimpanzees has been entertained recently as well (20), and so the fossil record and its interpretation give a range of 4.2-12.5 Ma.…”
mentioning
confidence: 99%
“…The degree of sexual dimorphism in A. anamensis and A. afarensis suggests intense one-onone male -male competition and perhaps a gorilla-like social structure (Leakey et al, 1998). Although other social structures are, of course, possible (Plavcan, 2000), a gorilla-like social structure is consistent with many features of human social organization.…”
Section: Figurementioning
confidence: 66%
“…Males and females of monogamous species, in contrast, tend to be similar in physical size (e.g., Leigh, 1995). When these patterns are compared to patterns of sexual dimorphism in the fossil record, inferences about the reproductive strategies of extinct hominids can be drawn (Foley, 1999;Leakey, Feibel, McDougall, & Walker, 1995;Leakey, Feibel, McDougall, Ward, & Walker, 1998).…”
Section: Originsmentioning
confidence: 99%
See 1 more Smart Citation